2019
DOI: 10.31557/apjcp.2019.20.11.3465
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Soluble HLA-G and HLA-G +3142G/C Polymorphism in Breast Cancer Patients Receiving Adjuvant Therapy in Tanzania

Abstract: Background: During cancer growth, immunosuppressive microenvironment is created that enables tumour cells to evade an eliminative immune response and hence manage to grow into malignancy. HLA-G, existing as either membrane-bound (mHLA-G) or soluble (sHLA-G) molecule is thought to be immunosuppressive and produced more by tumor cells. The +3142G/C polymorphism in HLA-G gene affects its expression, and G allele is considered to be a protective mutant allele associated with less expression of HLA-G. The implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Though, the few patients whose sHLA-G levels remained high were found to have had their cancers metastasized. Similarly, in our recent study, 82 we found a significantly lower amount of sHLA-G among breast cancer patients who had undergone mastectomy as compared to those who had not. Rutten et al 78 found a significant decline in sHLA-G levels following chemotherapy treatment of high-grade ovarian cancer, and the sHLA-G increased to almost the initial levels following recurrence.…”
Section: Diagnostic Prognostic and Therapeutic Implications Of Hla-g ...supporting
confidence: 81%
“…Though, the few patients whose sHLA-G levels remained high were found to have had their cancers metastasized. Similarly, in our recent study, 82 we found a significantly lower amount of sHLA-G among breast cancer patients who had undergone mastectomy as compared to those who had not. Rutten et al 78 found a significant decline in sHLA-G levels following chemotherapy treatment of high-grade ovarian cancer, and the sHLA-G increased to almost the initial levels following recurrence.…”
Section: Diagnostic Prognostic and Therapeutic Implications Of Hla-g ...supporting
confidence: 81%
“…In addition to thyroid cancer, plasma sHLA-G levels were also lower in breast cancer patients. However, these were non-treatment-naïve samples, thus the relationship between sHLA-G and breast cancer is unclear [ 44 ].…”
Section: Shla In Malignanciesmentioning
confidence: 99%
“…Extending upon this, the number of studies that perform a receiver operating characteristic (ROC) analysis (plotting the relation between sensitivity and specificity) to assess the discriminative power of sHLA as a biomarker is limited. Although only partially informative due to the lack of proper non-malignant control groups, the described area under the curve (AUC) for sHLA-G to discriminate cancer patients from healthy controls was significantly different from chance (AUC = 0.5) in all reporting studies and ranged from 0.6 to 0.842 [ 33 , 35 , 36 , 39 , 44 , 50 ]. From these studies, three report on a good discriminative power of sHLA-G between malignancy and other, non-malignant diseases, although two of those mixed non-malignant control samples with healthy controls for ROC analysis [ 35 , 36 , 39 ].…”
Section: Shla In Malignanciesmentioning
confidence: 99%